PENCEMARAN NAMA BAIK MELALUI PENYALAHGUNAAN TEKNOLOGI ARTIFICIAL INTELLIGENCE DALAM PENGEDITAN WAJAH DI INDONESIA - Chusnaniyah, Aziatul; Dluha, Muhammad; Qorib, Fathul (Program Studi Magister Hukum Universitas Malikussaleh, 2026)
The rapid development of Artificial Intelligence (AI) technology has significantly influenced various aspects of social life, particularly in the digital media environment. One prominent application of AI is facial editing technology, including deepfake, face swap, and image manipulation, which enables the creation of highly realistic visual content. However, the misuse of such technology poses serious risks, especially in relation to defamation. The dissemination of AI-manipulated visual content through digital platforms may harm an individual’s reputation and dignity on a massive scale. This phenomenon raises legal issues concerning the adequacy of defamation regulations in Indonesia’s digital legal framework. This research aims to analyze the legal regulation of defamation in Indonesia and to examine forms of AI misuse in facial editing that may result in defamation. The research employs a normative juridical method, focusing on statutory and conceptual approaches. The findings indicate that existing legal provisions under the Indonesian Criminal Code and the Law on Electronic Information and Transactions are generally applicable to AI-based defamation through legal interpretation. Nevertheless, the absence of specific regulations governing AI creates legal loopholes, particularly in law enforcement and evidentiary processes. Therefore, adaptive legal reform and strengthened law enforcement mechanisms are necessary to ensure legal certainty and effective protection in the digital era.